SINDROM MILLER FISHER SEBAGAI VARIAN SINDROM GUILLAN BARRE : LAPORAN KASUS - Lydia Susanti; Fadrian Herjunio (Yayasan Nusantara Hasana Berdikari, 2023)
Miller Fisher syndrome (MFS) is a rare variant of Guillan Barre Syndrome (GBS), with clinical symptoms of ophthalmoplegia, ataxia, areflexia. The diagnosis of MFS in this patient is based on a clear history supported by supporting examinations such as electrophysiological examination and CSF analysis. CSF analysis is often unsupportive at the onset of the disease, in which case the validated Brighton criteria may serve as a reference for establishing the diagnosis of GBS and its variants.